Raise Children into Responsible Muslim Adults - Fitrah Yuliawati; Ika Nuriyanti (Vicratina : Jurnal Ilmiah Keagamaan, 2018)
English is a foreign language for Indonesian students in Indonesia. It is given from junior high school to university. But now days English is also given in elementary school. The different material also used because of the different character of students. The aim of English program at elementary students is to enable them to comprehend oral and written expression. Teaching English for children is depending on the media that support the material. The used of media is the important thing to improve the ability of students. One of media that used is pictures, because in pictures children will find it easy to remember about the name of something. Children focus on some concrete things so that teacher should give the correct media that interest students to learn more about English. English as a subject dedicated to very young learners should be presented as interestingly as possible. The teachers’ creativity in creating attractive materials is very important to attract the learners’ attention.